Boosting antimicrobial activity of ciprofloxacin by functionalization of mesoporous silica nanoparticles - Mora, Blanca de Juan (2022)
UID/MAR/04292/2020 PEst-C/LA0006/2013 RECI/BBBBQB/0230/2012 MAR-02.01.01-FEAMP-0042–INOVA4AQUA 022161